ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШӘРИЯР»: ВАРИАНТЛАР АРАЛЫҚ УҚСАСЛЫҚ ҲӘМ ӨЗГЕШЕЛИКЛЕР - Кеңесбаева, Ш.К. (FAN va JAMIYAT, 2020)
The article typologically considers the variants of jiray Kulamet and Uteniyaz of the Karakalpak folk epic «Shariyar», investigates the issues of commonality and originality between the variants. Based on this comparative typological study, it is concluded that the version of the Kulamet jiray is one of the oldest copies, close to to the archetype and book versions